A new report concerning nuclear DNA content and premeiotic DNA synthesis in fungi - David D. Perkins (Fungal Genetics Reports, 1990)
R. Duran and P. M. Gray have published results of considerable interest that may escape notice because of the title and the journal ("Nuclear DNA, an adjunct to morphology in fungal taxonomy". Mycotaxon 36:205-219, 1989). Data are presented on nuclear DNA content of species of Neurospora and smut fungi and on the time of premeiotic DNA synthesis.